PENGGUNAAN KONSELING ONLINE DENGAN TEKNIK RELAKSASI PADA ORANG DALAM PENGAWASAN (ODP) COVID-19: SEBUAH STUDI KUALITATIF [USING ONLINE COUNSELING WITH RELAXATION TECHNIQUE FOR PERSON UNDER SURVEILLANCE COVID-19: A QUALITATIVE STUDY] - K Kasmi; N Nurjannah (Journal of Contemporary Islamic Counselling, 2021)
Coronavirus Disease 2019 (COVID-19) entered Indonesia since March 2020 which was previously found in Wuhan, one of the cities in China. This causes all activities to be carried out from home and requires all people to maintain a distance such as the educational process. This study aims to monitor the stages of online counseling being carried out and be alert to how online counseling indicators are carried out. The research method used is qualitative by using interviews and online observations to study the data. The results of this study indicate that the online and offline counseling stages have no basis, namely the initial stage for building relationships, the initial stage for confirming data and applying treatment, and the final stage for evaluation and follow-up. The implementation of online counseling on ODP COVID-19 has a positive impact because it is able to bring the subject to the desired change, namely returning to normal activities without feeling exposed to COVID-19 and being able to follow the learning process well.